2020
DOI: 10.1093/eurheartj/ehaa069
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bariatric surgery on long-term cardiovascular outcomes: a nationwide nested cohort study

Abstract: Aims This study aims to evaluate the long-term effect of bariatric surgery on cardiovascular outcomes of patients with obesity. Methods and results A nested cohort study was carried out within the Clinical Practice Research Datalink. The study cohort included the 3701 patients on the database who had undergone bariatric surgery and 3701 age, gender, and body mass index-matched controls. The primary endpoint was the composite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 24 publications
3
33
2
5
Order By: Relevance
“…This reduction in risk is in line with that reported for the metabolic surgery group in general as well as for patients with T2DM [ 18 21 ]. A recent publication by Aminian and colleagues reported a reduction in the risk for MACEs and mortality in patients with T2DM that underwent metabolic surgery [ 20 ].…”
Section: Discussionsupporting
confidence: 90%
“…This reduction in risk is in line with that reported for the metabolic surgery group in general as well as for patients with T2DM [ 18 21 ]. A recent publication by Aminian and colleagues reported a reduction in the risk for MACEs and mortality in patients with T2DM that underwent metabolic surgery [ 20 ].…”
Section: Discussionsupporting
confidence: 90%
“…A nationwide nested cohort study of 7402 patients (3701 undergoing bariatric surgery and 3701 not undergoing surgery) followed-up for a median 11.2 years found that bariatric surgery was associated with significantly lower incidence of fatal and non-fatal myocardial infarction and stroke, lower incident HF and mortality. 68 Bariatric surgery is not discussed in the current American or European HF guidelines, or in the current HT listing guidelines, though these more recent data may suggest bariatric surgery can be used as meaningful therapy, or a bridge to transplant, which has been shown to be safe and effective. 65 , 69.…”
Section: Bariatric Surgerymentioning
confidence: 99%
“…Considering that patients were followed during similar periods before (waiting list) and after (follow-up) bariatric surgery for comparison of information pre-and post-intervention, we obtained robust results indicating that bariatric surgery was efficient intervention to interrupt worsening of patients' health conditions, and to promote improvements in health outcomes related to hypertension and diabetes in association with reduction of direct health care costs after treatment, findings in accordance with previous evidence. 15,[19][20][21]23,24 Due to lack of previous evidence regarding impacts of bariatric surgery based on pre-and postintervention costs and multiple health outcomes using micro-costing approach at individual-level, the robust results provided by our estimates may provide real-world foundations for public policy decision making within Brazilian national health system, especially referring to intervention with significant potential for reduction of burden of diseases related to obesity. 71,72 The analysis was conducted on small sample of patients with moderate to severe obesity within one Brazilian hospital of reference who were on the waiting list for bariatric surgery, followed from 6month period before and after the bariatric surgery, extracted from a cohort of approximately 2,000 patients followed during 12 or more years.…”
Section: Characteristics Pre-and Post-surgerymentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Considering the rising costs of health care and the escalating burden of obesity in diverse countries, there has been increasing trends in examination of cost-effectiveness of health interventions towards prevention and treatment of obesity and its effects on comorbidities. [10][11][12][13][14][15] Recent evidence on the impacts of obesity-related interventions, including prevention [16][17][18] (promotion of physical activity and healthy eating) and treatment (medication and/or surgical procedures) strategies [19][20][21][22][23][24] , have demonstrated that efficacy of bariatric surgery with multi-disciplinary approach decreasing body weight and improving of health including cancer, cardiovascular events, T2DM, dyslipidemia, life expectancy, and quality of life. 5,23,[25][26][27][28] in the long run.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation